2020
DOI: 10.3389/fbioe.2020.584952
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Non-linear Dynamic Methods Toward Investigating Proprioception Impairment in Non-specific Low Back Pain Patients

Abstract: Central nervous system (CNS) uses vision, vestibular, and somatosensory information to maintain body stability. Research has shown that there is more lumbar proprioception error among low back pain (LBP) individuals as compared to healthy people. In this study, two groups of 20 healthy people and 20 non-specific low back pain (NSLBP) participants took part in this investigation. This investigation focused on somatosensory sensors and in order to alter proprioception, a vibrator (frequency of 70 Hz, amplitude o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The experimental set up in this study is similar to our prior investigation on chronic low back pain patients ( Shokouhyan et al, 2020 ) including male participants who suffered LBP at least three times in the recent year or one time in a 3 months duration. The participants were divided evenly between the two groups: an NSLBP group and a healthy control group based on two questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental set up in this study is similar to our prior investigation on chronic low back pain patients ( Shokouhyan et al, 2020 ) including male participants who suffered LBP at least three times in the recent year or one time in a 3 months duration. The participants were divided evenly between the two groups: an NSLBP group and a healthy control group based on two questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to maintain stability and balance to prevent falls in the elderly is critical. It is not surprising that many studies have identified lower back muscle weakness and balance problems (66,67) as the most important risk factors for falls (68). Furthermore, in COPD patients, the relationship between different components of balance and falling has been well investigated (29)(30)(31).…”
Section: Balance Deficitsmentioning
confidence: 99%
“…LBP patients may suffer from certain degrees of postural control abnormalities, mainly manifested as decreased trunk coupling ability, 7 impaired gait, 8 increased center of gravity and center of mass deviation, 9 prolonged or disappeared preactivation time of postural muscles, 10 proprioceptive disturbances, 11 decreased attention and executive ability, 12 and reorganized structural or functional of the central nervous system. 13 …”
Section: Introductionmentioning
confidence: 99%